2023
DOI: 10.3390/molecules28114548
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Anti-Cancer Properties of Amygdalin Extracted from Three Cassava Varieties Cultivated in Benin

Halfane Lehmane,
Arnaud N. Kohonou,
Atchadé Pascal Tchogou
et al.

Abstract: Given that cancer is a disease that is rampant in the world and especially in Africa, where the population has enormous difficulty treating it, plants are a safer and less expensive alternative. Cassava is a plant species valued in Benin because of its numerous medicinal and nutritional virtues. This study evaluated the biological activities of amygdalin from the organs of three cassava varieties most commonly produced in Benin (BEN, RB, and MJ). HPLC analysis was used to quantify amygdalin in cassava organs a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In this work, an obvious variation on the contents of amygdalin (0.051−5.314%) and mandelonitrile (0.004−0.317%) was detected in seeds across different accessions of P. sibirica (Fig. 1 a), as was also noted in several Prunus species from different regions [ 55 59 ]. Also, both mandelonitrile and amygdalin accumulation specially responded to seed development of P. sibirica (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…In this work, an obvious variation on the contents of amygdalin (0.051−5.314%) and mandelonitrile (0.004−0.317%) was detected in seeds across different accessions of P. sibirica (Fig. 1 a), as was also noted in several Prunus species from different regions [ 55 59 ]. Also, both mandelonitrile and amygdalin accumulation specially responded to seed development of P. sibirica (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Among these, young stems and fresh cassava leaves exhibited the highest concentrations of amygdalin, with 11,142.99 µg per 10 g and 9251.14 µg per 10 g, respectively. The antioxidant activity results showed that the amygdalin extracts were DPPH radical scavengers with IC50 values ranging from 0.18 mg/mL to 2.35 mg/mL [42]. Based on these results, it can be concluded that these extracts possess a considerably high concentration of amygdalin.…”
Section: Antioxidant Activity Of Amygdalinmentioning
confidence: 79%
“…In recognition of the abundance of phytochemicals in cassava, it is recognized as a plant that is both edible and therapeutic. According to research, cassava leaves, stems, and extracts have wound-healing, anticancer, and hypotensive properties (Lehmane et al, 2023). Cassava might be used as a nutritious meal with careful processing to remove contaminants, and its bioactive components show promise for therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%